Anti-angiogenic agents in the age of resistance to immune checkpoint inhibitors: Do they have a role in non-oncogene-addicted non-small cell lung cancer?. (June 2020) - Popat, Sanjay; Grohé, Christian; Corral, Jesus; Reck, Martin; Novello, Silvia; Gottfried, Maya; Radonjic, Dejan; Kaiser, Rolf
Highlights: The majority of patients with advanced NSCLC relapse on immunotherapy. Evidence on optimal systemic therapy after progression on immunotherapy is limited. Targeting VEGF-promoted angiogenesis may reduce immunosuppression. Anti-angiogenics may reinstate and enhance the effect of subsequent therapies. Abstract: The introduction of licensed front-line immunotherapies has heralded a new era for the treatment of non-oncogene-addicted, advanced non-small cell lung cancer (NSCLC). Yet as with all evolutions in clinical management, changes in practice can outpace the availability of the clinical evidence needed to inform subsequent therapeutic decision making. At the time of writing, there is limited available evidence on the optimum therapeutic options after progression on immunotherapy. Further research is needed to define mechanisms of immunotherapy resistance in patients with advanced NSCLC, and to understand the implications for subsequent treatment response. Pending the availability of robust clinical data and proven therapeutic options to underpin an optimized therapeutic pathway after progression on immunotherapy, attention must turn to the potential utility of currently licensed agents and any available supporting clinical data in this setting. Within this context we review the mechanistic arguments and supporting evidence for the use of anti-angiogenic agents as a means of targeting immunosuppression within the tumor microenvironment. We consider whether VEGF inhibition may help to normalize the tumor vasculature and to address immunosuppression – reinstating, and potentially enhancing, the effect of subsequent therapies. We also highlight evidence needs and signpost ongoing trials that should enable current clinical opinion in this area to be replaced by robust, evidence-based guidance.